2015
DOI: 10.1038/ki.2014.220
|View full text |Cite
|
Sign up to set email alerts
|

Renal denervation has blood pressure–independent protective effects on kidney and heart in a rat model of chronic kidney disease

Abstract: We elucidate the underlying mechanisms of bidirectional cardiorenal interaction, focusing on the sympathetic nerve driving disruption of the local renin-angiotensin system (RAS). A rat model of N(ω)-nitro-L-arginine methyl ester (L-NAME; a nitric oxide synthase inhibitor) administration was used to induce damage in the heart and kidney, similar to cardiorenal syndrome. L-NAME induced sympathetic nerve-RAS overactivity and cardiorenal injury accompanied by local RAS elevations. These were suppressed by bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…5). This counterintuitive AGT mRNA suppression in the kidney was also observed in a rat model treated with a nitric oxide synthase inhibitor in our previous report (4). This suggests filtration of circulating AGT into the urine enhances reabsorption of AGT at proximal convoluted tubules and leads to suppression of the local generation of AGT at proximal convoluted tubules in a negative feedback mechanism (Fig.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…5). This counterintuitive AGT mRNA suppression in the kidney was also observed in a rat model treated with a nitric oxide synthase inhibitor in our previous report (4). This suggests filtration of circulating AGT into the urine enhances reabsorption of AGT at proximal convoluted tubules and leads to suppression of the local generation of AGT at proximal convoluted tubules in a negative feedback mechanism (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Rat tissues and paraffin-embedded human renal biopsy specimens were prepared and stained as previously described (4). Briefly, for staining with anti-human AGT, anti-mouse/ rat AGT, anti-desmin, anti-podocin, and anti-albumin antibodies, using paraffin-embedded sections, heat-induced antigen retrieval was performed by autoclaving slides for 20 min in citrate buffer (pH 6.0, Wako Pure Chemical Industries, Osaka, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased sympathetic activity contributes to the progression of CKD and to the pathogenesis of hypertension. Several studies have shown that the inhibition of sympathetic excitation, either by renal denervation or pharmacologic agents, attenuates renal damage independent of blood pressure effects in animal models of CKD [2,3,4,5]. The role of renal sympathetic nerves has important clinical implications, and percutaneous catheter-based renal denervation has recently become available to disrupt renal sympathetic nerves.…”
Section: Introductionmentioning
confidence: 99%